SOCIODEMOGRAPHIC FACTORS AND CHARACTERISTICS OF PREGNANT WOMEN WITH ANEMIA - Yunri Merida; Shandy Wigya Mahanan; Warsiyati Warsiyati; Bima Suryantara (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Pregnancy anemia impacts the risk of postpartum hemorrhage, low birth weight (LBW), and stunting. Based on WHO data, the prevalence of anemia in pregnant women globally is 40-44% in 2024. In the Ngluwar Community Health Center working area, the prevalence of anemia decreased from 17.6% in 2023 to 11.5% in 2024, but by September 2025 it had increased to 12.5%. The purpose of this study was to identify the dominant factors associated with the incidence of anemia seen from sociodemographic factors and characteristics of pregnant women with anemia. This study used a quantitative approach with an observational analytical design with a sample of 54 pregnant women in the first trimester by random sampling. This research instrument used a questionnaire and a KIA book. The results of the study showed that most pregnant women who experienced anemia were aged 20-35 years, multiparous, had income below the minimum wage, had secondary education, and were unemployed. The most dominant factor influencing anemia was age. It is recommended that pregnant women receive sufficient education about anemia.